Pengembangan Sistem Penjadwalan Pelajaran Sekolah Di SMPN 1 Sedati Kabupaten Sidoarjo Berbasis Website - Naufal Abdillah; Aidil Primasetya Armin; Bagus Hardiansyah (International Conference of Innovation and Community Engagement, 2024)
Timetable management is one of the major challenges faced by many schools, including SMPN 1 Sedati in Sidoarjo Regency. The manual process, which is time-consuming and prone to errors, often creates obstacles in creating effective schedules, resulting in several days of completion. To address this issue, a web-based scheduling system was developed to simplify and expedite the scheduling process. This system is designed to automatically generate schedules within a maximum of 30 minutes, considering factors such as teacher availability and curriculum requirements. Through this community service project, the system is expected to assist the school in managing class schedules more efficiently, optimizing both time and resources. The implementation results show that the system significantly reduces the time needed for schedule creation while providing flexibility in school data management.